PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN DI UPT PUSKESMAS SEI LEKOP - R.Sihombing, April Hadi; Raymod, Raymond (SCIENTIA JOURNAL, 2021)
This study was io determine the effect of Service quality and facilities for satisfaction in UPT Puskesmas Sei Lekop, the population of this study was all of patient visited at UPT Puskesmas Sei Lekop in 2019, the number of samples is calculated using slovin formula. So, the sample in this study was 330. Data analysis methods use descriptive analysis, data quality test, classic assumption test, regression and hypothesis testing with help of SPSS. The result of the data analysis in this study show that service quality has a significant positive affect on patient satisfaction with a value of 10,9239 > t table 1,967. Facilities has a significant positive affect on patient satisfaction with a value 6,653 > t table 1,967. Lastly, independent variables service quality and facilities simultaneously affect patient satisfaction with a F count of 187,294 > F table 3,02. The result of the determinant coefficient analysis obtained 0,534 or 53,4%, which means the contribution of 53,4% the rest is influenced by other variables of this study.